2008
DOI: 10.1152/ajpcell.90638.2007
|View full text |Cite
|
Sign up to set email alerts
|

CaM kinase IIδ2-dependent regulation of vascular smooth muscle cell polarization and migration

Abstract: Previous studies indicate involvement of the multifunctional Ca2+/calmodulin-dependent protein kinase II (CaMKII) in vascular smooth muscle (VSM) cell migration. In the present study, molecular loss-of-function studies were used specifically to assess the role of the predominant CaMKII delta2 isoform on VSM cell migration using a scratch wound healing assay. Targeted CaMKII delta2 knockdown using siRNA or inhibition of activity by overexpressing a kinase-negative mutant resulted in attenuation of VSM cell migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 53 publications
2
73
0
Order By: Relevance
“…6 as the Endogenous HUVEC Isoform-To design specific molecular approaches for probing functions of endogenous CaMKII in endothelial cells, we first identified the CaMKII isoform(s) expressed in several cell lines by Western blotting with CaMKII subtype-specific antibodies. Blotting with a antibody recognizing all CaMKII isoforms (11-14, 19, 22), indicated that the predominant isoform expressed in primary cultures of endothelial cells has an apparent molecular mass of 50 kDa, smaller than the predominant 52-kDa isoform in cultured rat VSM, which we previously identified as the CaMKII␦ 2 variant (11,12,14,15) (Fig. 1A, top panel).…”
Section: Measurement Of Transendothelial Electric Resistance (Teer)-ementioning
confidence: 85%
“…6 as the Endogenous HUVEC Isoform-To design specific molecular approaches for probing functions of endogenous CaMKII in endothelial cells, we first identified the CaMKII isoform(s) expressed in several cell lines by Western blotting with CaMKII subtype-specific antibodies. Blotting with a antibody recognizing all CaMKII isoforms (11-14, 19, 22), indicated that the predominant isoform expressed in primary cultures of endothelial cells has an apparent molecular mass of 50 kDa, smaller than the predominant 52-kDa isoform in cultured rat VSM, which we previously identified as the CaMKII␦ 2 variant (11,12,14,15) (Fig. 1A, top panel).…”
Section: Measurement Of Transendothelial Electric Resistance (Teer)-ementioning
confidence: 85%
“…In our hands, overexpression of Fyn had detrimental effects on VSM proliferation and viability. 4 Based on previous studies and the fact that Fyn has dual palmitoylation sites in its SH4 domain that target it directly to lipid rafts (39), Fyn association with the Golgi and peripheral membrane as shown in Fig. 4 is not surprising.…”
Section: Discussionmentioning
confidence: 78%
“…To determine whether localization of CaMKII␦ 2 and/or Fyn is dependent on activation conditions, VSM cells were stimulated with PDGF (100 ng/ml), a stimulus known to activate CaMKII and to stimulate migration in VSM cells (4). Within minutes after the addition of PDGF, Fyn and, to a lesser extent, CaMKII␦ 2 localized at cell margins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations